The Impact of THC and CBD in Schizophrenia: A Systematic Review - Ahmed, Saeed; Roth, Robert M.; Stanciu, Corneliu N.; Brunette, Mary F. (Frontiers in Psychiatry, 2021)
Background: People with schizophrenia are more likely to develop cannabis use disorder (CUD) and experience worse outcomes with use. Yet as cannabis is legalized for medical and recreational use, there is interest in its therapeutic potential. Objectives: To conduct a systematic review summarizing the design and results of controlled trials using defined doses of THC and CBD in schizophrenia. Method: A keyword search of eight online literature databases identified eleven eligible reports. Results: One placebo controlled trial (13 stable patients without CUD) found that intravenous THC increased psychosis and worsened learning/recall. Two reports of a functional magnetic resonance (fMRI) study of smoked or oral THC in 12 abstinent patients with schizophrenia and CUD found no change in symptoms and cognition, and an amelioration of impaired resting state brain function in areas implicated in reward function and the default mode network. One four-week trial in acutely psychotic inpatients without CUD (mean age 30y) found 800 mg CBD to be similarly efficacious to amisupride in improving psychosis and cognition. Two six-week studies of CBD augmentation of antipsychotics in stable outpatients reported mixed results: CBD 600 mg was not more effective than placebo; CBD 1,000 mg reduced symptoms in a sample that did not exclude cannabis use and CUD. A brain fMRI and proton magnetic resonance spectroscopy study of single dose CBD in a sample that did not exclude CUD and cannabis use found that CBD improved symptoms and brain function during a learning/recall and was associated with increased hippocampal glutamate. Discussion: There is substantial heterogeneity across studies in dose, method of drug delivery, length of treatment, patient age, whether patients with cannabis use/CUD were included or excluded, and whether patients were using antipsychotic medication. Conclusion: There is insufficient evidence for an effect of THC or CBD on symptoms, cognition, and neuroimaging measures of brain function in schizophrenia. At this time, research does not support recommending medical cannabis (THC or CBD) for treating patients with schizophrenia. Further research should examine THC and CBD in schizophrenia with and without comorbid CUD and consider the role of CBD in mitigating symptom exacerbation from THC.